1998
DOI: 10.1021/jp9809890
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Hybrid Orbital (GHO) Method for the Treatment of Boundary Atoms in Combined QM/MM Calculations

Abstract: A generalized hybrid orbital (GHO) method has been developed at the semiempirical level in combined quantum mechanical and molecular mechanical (QM/MM) calculations. In this method, a set of hybrid orbitals is placed on the boundary atom between the QM and MM fragments, and one of the hybrid orbitals participates in the SCF calculation for the atoms in the QM region. The GHO method provides a well-defined potential energy surface for a hybrid QM/MM system and is a significant improvement over the “link-atom” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
544
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 506 publications
(549 citation statements)
references
References 28 publications
(57 reference statements)
3
544
0
2
Order By: Relevance
“…The third category is the hybrid-orbital approach which employs either hybrid or localized frozen orbitals on the QM atom of the QM-MM covalent pair. 34,35 The link atom approach is by far the simplest to implement, and if used carefully can give satisfactory results. 36 A recent study by König et al on the effect of different QM/MM frontier treatments with SCC-DFTB as the QM method also concluded that the effect of using different link atom schemes in QM/MM simulations is rather small, especially in reactions that conserve the total charge, and emphasizes that other technical details such as the treatment of long-range electrostatics can often play a more important role.…”
Section: Qm/mmmentioning
confidence: 99%
“…The third category is the hybrid-orbital approach which employs either hybrid or localized frozen orbitals on the QM atom of the QM-MM covalent pair. 34,35 The link atom approach is by far the simplest to implement, and if used carefully can give satisfactory results. 36 A recent study by König et al on the effect of different QM/MM frontier treatments with SCC-DFTB as the QM method also concluded that the effect of using different link atom schemes in QM/MM simulations is rather small, especially in reactions that conserve the total charge, and emphasizes that other technical details such as the treatment of long-range electrostatics can often play a more important role.…”
Section: Qm/mmmentioning
confidence: 99%
“…The entire chemical system was divided into a QM region, treated by the AM1 semiempirical MO method, and a MM region comprising the rest of the protein (CHARMM26 potentials) 11 and the water molecules. The generalized hybrid orbital (GHO) 12 method was used to treat those covalent bonds crossing the boundary between the QM and the MM regions. The QM region, formed by the dihydronicotinamide and the ribose ring of the NADH, Arg171, Arg109, the pyruvate and the His195 contained a total of 78 atoms.…”
mentioning
confidence: 99%
“…As mentioned above, the link atom scheme has been the most popular with semiempirical QM/MM potentials, although other algorithms have been proposed. These include methods based upon hybrid orbitals 51,55,56 and those that use pseudoatoms. 57 Although these methods are more elegant in that they dispense with the fictitious link atoms in the QM region, they have not yet been shown to be consistently better than the newer link atom approximations, 58,59 which are more versatile and, in comparison to the hybrid orbital methods, simpler to implement.…”
Section: Hybrid Potential Methodsmentioning
confidence: 99%